ECONOMIC LEVERS AND INCENTIVES OF ECONOMIC DEVELOPMENT OF THE FOOD REGION OF THE REGION - Рогатіна, Л. П. (Podilian Bulletin: Agriculture, Engineering, Economics, 2017)
The article defines the main approaches to determining the essence of economic incentives, their advantages and disadvantages. The main components of the formation of food security are considered. It has been proved that the development and implementation of joint regional projects, the introduction of innovations in the production sector, the creation of new products, the intensification of internal regional cooperation (interregional, intermunicipal), etc., are becoming extremely important for stimulating economic development. Areas for the activation of the local economic initiative have been formed, the components of the processes for stimulating economic development have been determined. For successful implementation of the strategy of managing the economic development of the region, it is important to create a model for effective functioning. In modern conditions of globalization, such a model should take into account the historical features of the region, the resource potential, principles and methods of managing financial, social, organizational aspects of economic activity. Formation of regional development paths requires the development of an appropriate model and modeling of processes